Epidermoid cyst of the brain: A common cystic lesion in rare location (Indian Journal of Case Reports, 2024)
Epidermoid cysts are common benign tumors comprising around 1% and 2% of all intracranial tumors. Their usual locations include the parasellar region and cerebellopontine angle, and less commonly, the Sylvian fissure, suprasellar region, cerebral, and cerebellar hemispheres. Epidermoid cysts located in the brain stem are rare. These epidermoid cysts are similar to epidermoids arising in the skin which contain cheesy and flaky-white soft pultaceous material. Epidermoid cysts are very slow-growing tumors having a similar growth pattern of the epidermal cells of the skin and develop from the remnants of epidermal elements during the closure of the neural groove and disjunction of the surface ectoderm with neural ectoderm between the 3rd and 5th weeks of embryonic life. The ideal treatment of choice is the removal of cystic components with the complete resection of the capsule. We are presenting an interesting case of an epidermoid cyst in the frontal lobe in a 42-year-old male along with radiological investigations.